Long term metabolic and renal outcomes of kidney donors compared to controls with excellent kidney function - Ayelet Grupper; Yoel Angel; Aharon Baruch; Idit F. Schwartz; Doron Schwartz; Richard Nakache; Yaacov Goykhman; Paulina Katz; Ido Nachmany; Nir Lubezky; Talia Weinstein; Moshe Shashar; et al. (BMC Nephrology, 2019)
Abstract Background Only few studies of living kidney donors have included controls that were similarly healthy, including excellent kidney function. Methods In this study, we aimed to estimate long term metabolic and renal outcome in a cohort of 211 living donors compared to two control groups: paired-matched controls, and another control group of 2534 healthy individuals with excellent kidney function. Results Donors presented with higher estimated Glomerular Filtration Rate (eGFR): (97.6 ± 15.2 vs 96.1 ± 12.2 vs 94.5 ± 12.4 ml/min/1.73m2) and lower urine albumin to creatinine ratio (UACR) (4.3 ± 5.9 vs 5.9 ± 6.1 vs 6.1 ± 6.9 mg/g) for donors, matched controls and healthy controls, respectively (p <  0.001). In a mean follow up period of 5.5 for donors, donors presented with positive eGFR slopes during the first 3 years post donation, followed by negative slopes, compared to constantly negative slopes presented in the control group (p <  0.05). The variables related to the slope were being a donor, baseline eGFR, Body Mass Index (BMI) and age but not eGFR on the last day of follow-up or increased delta UACR. There was a significant increase in UACR in donors, as well as a higher rate of albuminuria, associated with a longer time since donation, higher pre-donation UACR and higher pre-donation BMI. Healthy controls had a lower BMI at baseline and gained less weight during the follow up period. Donors and controls had similar incidence of new onset diabetes mellitus and hypertension, as well as similar delta systolic and diastolic blood pressure. Donors were more likely to develop new onset metabolic syndrome, even after adjustment for age, gender and BMI. The higher incidence of metabolic syndrome resulted mainly from increased triglycerides and impaired fasting glucose criteria. However, prevalence of major cardiovascular events was not higher in this group. Conclusions Donors are at increased risk to develop features of the metabolic syndrome in addition to the expected mild reduction of GFR and increased urine albumin excretion. Future studies are needed to explore whether addressing those issues will impact post donation morbidity and mortality.